Sanitasi Lingkungan, Pemberian Asi Dan Budaya Maruas Di Masyarakat Banjar Meningkatkan Risiko Diare Pada Balita - erni yuliastuti; Tut barkinah (Jurnal Skala Kesehatan, 2019)
Diarrhea is an important health issue because it is the third major contributor to toodler morbidity and mortality in Indonesia (Basic Health Research, 2010). The incidence of diarrhea in Banjar Regency was ranked 2nd after Banjarmasin city. Diarrhea in Martapura Health Center amounted to 306 people, ranked second after the Gambut Health Center, as many as 936 people (Banjar Regency Health Office,2013). Diarrheaas a top 10 most diseases and the highest prevalence occurs in toddlers. The risk of diarrhea related to knowledge, behaviour of exclusive breastfeeding and environmental sanitation. These three factors will interact with human behavior that could have an impact on the incidence of diarrhea. The purpose of this research was to analyze knowledge, exclusive breastfeeding, environmental sanitation and maternal characteristics, culture about maruas with the incidence of diarrhea. This research is an analytic survey type with cross sectional design.The instrument used is a questionnaire containing a list of questions and medical record. The population of the research was mothers who took their children to visit the IMCI Polyclinic at Martapura Health Center in 2016. The sample is the mother who visited theIMCI Polyclinic in the work area of Martapura Health Center and large sample as many as 100 people. Data analysis using the Chi Square Test and OR. The results showed that there was a relationship between the incidence of diarrhea with age (ρ = 0,000), education (ρ = 0,021), employment (ρ = 0,026) OR = 4,012, knowledge (ρ = 0,001), exclusive breastfeeding (ρ = 0,013) OR = 4,573 , environmental sanitation (ρ = 0,000) OR = 16,579, maruas culture (ρ = 0,020) OR = 3,250. The risk of the highest incidence of diarrhea by environmental sanitation factors is 16,579 risky timesoccur in families with unhealthy home environmental sanitation. Keywords: Diarrhea; Sanitation; Breastfeeding; Culture